Freedom Begins Here : Tool Kit - Smalley, Gary; Cunningham, Ted; Laaser, Mark (Gray Communications, Inc., 2008)
Freedom Begins Here is a dynamic series of DVD "ToolKits" designed specifically to empower individuals and churches to face the crisis of pornography and sexual addiction head on. Co-hosted by America's Leading marriage expert, Dr. Gary Smalley, and Pastor Ted Cunningham, Freedom Begins Here is filled with relevant, life-changing material. With in-depth teaching from Dr. Mark Laaser, recognized as the leading Christian authority on sexual addiction, Freedom Begins Here stands in the gap by providing the most complete resource available to help people find freedom from the stronghold of pornography and sexual addiction. This Church ToolKit equips churches with the resources needed to recognize and confront pornography and sexual addiction, as well as beginning the journey of recovery for those in need of help. Contents: